Sodium-Related Adaptations to Drought: New Insights From the Xerophyte Plant Zygophyllum xanthoxylum - Xi, Jie-Jun; Chen, Hong-Yu; Bai, Wan-Peng; Yang, Rong-Chen; Yang, Pei-Zhi; Chen, Ru-Jin; Hu, Tian-Ming; Wang, Suo-Min (Frontiers in Plant Science, 2018)
Understanding the unusual physiological mechanisms that enable drought tolerance in xerophytes will be of considerable benefit because of the potential to identify novel and key genetic elements for future crop improvements. These plants are interesting because they are well-adapted for life in arid zones; Zygophyllum xanthoxylum, for example, is a typical xerophytic shrub that inhabits central Asian deserts, accumulating substantial levels of sodium (Na+) in its succulent leaves while growing in soils that contain very low levels of this ion. The physiological importance of this unusual trait to drought adaptations remains poorly understood, however. Thus, 2-week-old Z. xanthoxylum plants were treated with 50 mM NaCl (Na) for 7 days in this study in order to investigate their drought tolerance, leaf osmotic potential (Ψs) related parameters, anatomical characteristics, and transpiration traits. The results demonstrated that NaCl treatment significantly enhanced both the survivability and durability of Z. xanthoxylum plants under extreme drought conditions. The bulk of the Na+ ions encapsulated in plants was overwhelmingly allocated to leaves rather than roots or stems under drought conditions; thus, compared to the control, significantly more Na+ compared to other solutes such as K+, Ca2+, Cl-, sugars, and proline accumulated in the leaves of NaCl-treated plants and led to a marked decrease (31%) in leaf Ψs. In addition, the accumulation of Na+ ions also resulted in mesophyll cell enlargement and leaf succulence, enabling the additional storage of water; Na+ ions also reduced the rate of water loss by decreasing stomatal density and down-regulating stomatal aperture size. The results of this study demonstrate that Z. xanthoxylum has evolved a notable ability to utilize Na+ ions to lower Ψs, swell its leaves, and decrease stomatal aperture sizes, in order to enable the additional uptake and storage of water and mitigate losses. These distinctive drought adaption characteristics mean that the xerophytic plant Z. xanthoxylum presents a fascinating case study for the potential identification of important and novel genetic elements that could improve crops. This report provides insights on the eco-physiological role of sodium accumulation in xerophytes adapted to extremely arid habitats.